A stepwise psychotherapy intervention for reducing risk in coronary artery disease (SPIRR-CAD): results of an observer-blinded, multicenter, randomized trial in depressed patients with coronary artery disease - Herrmann-Lingen, Christoph; Beutel, Manfred E.; Bosbach, Alexandra; Deter, Hans-Christian; Fritzsche, Kurt; Hellmich, Martin; Jordan, Jochen; Jünger, Jana; Ladwig, Karl-Heinz; Michal, Matthias; Petrowski, Katja; Pieske, Burkert; et al. (Psychosomatic medicine, 2016)
Background - Depression predicts adverse prognosis in patients with coronary artery disease (CAD), but previous treatment trials yielded mixed results. We tested the hypothesis that stepwise psychotherapy improves depressive symptoms more than simple information. - Methods - In a multicenter trial, we randomized 570 CAD patients scoring higher than 7 on the Hospital Anxiety and Depression Scale-depression subscale to usual care plus either one information session (UC-IS) or stepwise psychotherapy (UC-PT). UC-PT patients received three individual psychotherapy sessions. Those still depressed were offered group psychotherapy (25 sessions). The primary outcome was changed in the Hospital Anxiety and Depression Scale-depression scores from baseline to 18 months. Preplanned subgroup analyses examined whether treatment responses differed by patients' sex and personality factors (Type D). - Results - The mean (standard deviation) depression scores declined from 10.4 (2.5) to 8.7 (4.1) at 18 months in UC-PT and from 10.4 (2.5) to 8.9 (3.9) in UC-IS (both p < .001). There was no significant group difference in change of depressive symptoms (group-by-time effect, p = .90). Preplanned subgroup analyses revealed no differences in treatment effects between men versus women (ptreatment-by-sex interaction = .799) but a significant treatment-by-Type D interaction on change in depressive symptoms (p = .026) with a trend for stronger improvement with UC-PT than UC-IS in Type D patients (n = 341, p = .057) and no such difference in improvement in patients without Type D (n = 227, p = .54). - Conclusions - Stepwise psychotherapy failed to improve depressive symptoms in CAD patients more than UC-IS. The intervention might be beneficial for depressed CAD patients with Type D personality. However, this finding requires further study. - Trial Registration:www.clinicaltrials.gov NCT00705965; www.isrctn.com ISRCTN76240576.